2020
DOI: 10.1016/j.ijhcs.2019.102377
|View full text |Cite
|
Sign up to set email alerts
|

Augmented visualization cues on primary flight display facilitating pilot's monitoring performance

Abstract: There have been many aviation accidents and incidents related to mode confusion on the flight deck. The aim of this research is to evaluate human-computer interactions on a newly designed augmented visualization Primary Flight Display (PFD) compared with the traditional design of PFD. Based on statistical analysis of 20 participants interaction with the system, there are significant differences on pilots' pupil dilation, fixation duration, fixation counts and mental demand between the traditional PFD design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…In this paper, the authors attempt to address some of the limitations found in mathematical models of the human pilot by using eye tracking data to provide insight into the way the pilot uses the available information. Although numerous studies have been carried out using eye-tracking for various purposes in aviation, for example recognising scan patterns of a remote air traffic control by a single controller [10], flight deck design [11], augmented reality (AR) in Primary Flight Display (PFD) [9], air traffic controller's situation awareness [7] and understanding human behaviour during aircraft-pilot coupling events [8], there has been limited transfer of this knowledge into the mathematical formulation of pilot behaviour. In this study the authors synchronise temporal and spatial eye-tracking data with aircraft data to study scenarios where the pilot is given an urgent safety critical task.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the authors attempt to address some of the limitations found in mathematical models of the human pilot by using eye tracking data to provide insight into the way the pilot uses the available information. Although numerous studies have been carried out using eye-tracking for various purposes in aviation, for example recognising scan patterns of a remote air traffic control by a single controller [10], flight deck design [11], augmented reality (AR) in Primary Flight Display (PFD) [9], air traffic controller's situation awareness [7] and understanding human behaviour during aircraft-pilot coupling events [8], there has been limited transfer of this knowledge into the mathematical formulation of pilot behaviour. In this study the authors synchronise temporal and spatial eye-tracking data with aircraft data to study scenarios where the pilot is given an urgent safety critical task.…”
Section: Introductionmentioning
confidence: 99%
“…It can be influenced by internal aspects such as an individual's motivation or their past experience and ability, as well as external aspects such as the type, novelty, difficulty, and number of tasks that an individual completes (Hart, 1982;Meshkati, 1988). Originally rooted in attempts to measure the effort of flight-related tasks (see e.g., Li et al, 2020), the practice of assessing workload also became more and more relevant in contexts that transcend aviation. For example, due to the rapid technological advancements and the growing number of novel systems that aim at enhancing, among other factors, convenience, productivity and efficiency, it became increasingly relevant to scrutinize the workload demands of all sorts of information systems.…”
Section: Workloadmentioning
confidence: 99%
“…Domains in these environments tend to be dynamic and highly uncertain (Chmielewski et al 2018). The main task in the environment is operational complexity (Endsley and Rodgers 1994b), requiring operators to interpret various information at a speci c time to face unexpected technical errors (Li et al 2020). Previous researchers said there had not been agreed on universally embraced measurements.…”
Section: Related Studymentioning
confidence: 99%